Degeneration of white matter and gray matter revealed by diffusion tensor imaging and pathological mechanism after spinal cord injury in canine - Liu, Chang‐Bin (CNS Neurosci Ther, 2018)
AIM: Exploration of the mechanism of spinal cord degeneration may be the key to treatment of spinal cord injury (SCI). This study aimed to investigate the degeneration of white matter and gray matter and pathological mechanism in canine after SCI. METHODS: Diffusion tensor imaging (DTI) was performed on canine models with normal (n = 5) and injured (n = 7) spinal cords using a 3.0T MRI scanner at precontusion and 3 hours, 24 hours, 6 weeks, and 12 weeks postcontusion. The tissue sections were stained using H&E and immunohistochemistry. RESULTS: For white matter, fractional anisotropy (FA) values significantly decreased in lesion epicenter, caudal segment 1 cm away from epicenter, and caudal segment 2 cm away from epicenter (P = 0.003, P = 0.004, and P = 0.013, respectively) after SCI. Apparent diffusion coefficient (ADC) values were initially decreased and then increased in lesion epicenter and caudal segment 1 cm away from epicenter (P < 0.001 and P = 0.010, respectively). There are no significant changes in FA and ADC values in rostral segments (P > 0.05). For gray matter, ADC values decreased initially and then increased in lesion epicenter (P < 0.001), and overall trend decreased in caudal segment 1 cm away from epicenter (P = 0.039). FA values did not change significantly (P > 0.05). Pathological examination confirmed the dynamic changes of DTI parameters. CONCLUSION: Diffusion tensor imaging is more sensitive to degeneration of white matter than gray matter, and the white matter degeneration may be not symmetrical which meant the caudal degradation appeared to be more severe than the rostral one.